Pengaruh Penyuluhan KB dalam Pandangan Islam terhadap Keikutsertaan Pemilihan Kontrasepsi bagi Calon Akseptor di Dusun Jabung Yogyakarta Indonesia - Nelli Yendena; Retno Mawarti; Jannatul Husna (Politeknik Kesehatan Kartini Bali, 2022)
Based on the Population Growth Rate (LPP) data in 2018, the number of births in Indonesia was 5 million (1.28%) per year. One of the reasons is the lack of knowledge and participation of childbearing-age couples in contraceptive selection. They were given Islamic family planning (FP) counseling because most of Indonesia's population is Muslim. This study aims to determine the effect of FP counseling in the Islamic view on participation in contraceptive selection for prospective FP acceptors in Jabung, Pandowoharjo, and Sleman Yogyakarta. Pre-experimental research methods with on group pretest-posttest design. The Instrument was a questionnaire. The population was 49 childbearing women who did not use any kind of contraception and used total sampling. Bivariate analysis techniques used the Wilcoxon test. The average score of participation of prospective FP acceptors in choosing contraceptives before and after FP counseling in the Islamic view was increased from 57.76% to 82.29%, which showed a difference of 30.53. Wilcoxon test obtained z significance value which showed that FP counseling in the Islamic view was an effect on the participation in contraceptive selection for prospective FP acceptors at 0,000 with p value 0,000 <0.005.